Strengths and weaknesses of the German translation of the Inflexible Eating Questionnaire and of eating disorder assessment in general - Schultz, Anna; Maurer, Linda; Alexandrowicz, Rainer W. (Frontiers in Psychology, 2022)
The present article introduces the German translation of the Inflexible Eating Questionnaire (IEQ-G), performs a psychometric evaluation, and explores the relationship of Inflexible Eating to Obsessive-Compulsive (OC) symptoms and the subscales of the Eating Disorder Examination – Questionnaire (EDE-Q). SEM analyses showed that the IEQ-G allows for calculating a total score and invariance tests were mostly promising. As a side result, the original 4-factorial structure of the EDE-Q could not be replicated, but a 3 dimensional solution proved convincing. From a psychometric point of view, the IEQ-G outperformed the EDE-Q. On a latent level, Inflexible Eating was remarkably strong related to OC-symptoms and the EDE-Q subscales. The detail analyses revealed that ED assessment in general lacks subgroup-specific aspects, for instance, regarding gender or dietary preferences, important for early diagnosis and screening of EDs. The IEQ-G proved applicable in a German speaking adult population and recommends itself for cross-cultural studies.